Optimizing digital transformation as a destination branding strategy for Balkondes Karanganyar, Borobudur, Magelang - Ardhin Primadewi; Syahidan C Rohmana; Damas A Karim; Dianita Yuswanti; Septiawan Rofendi (Community Empowerment, 2022)
Borobudur Village Economic Center (Balkondes), is a CSR from the Ministry of SOEs that provides tourism icons to selected villages around the Borobudur Temple. Balkondes Karanganyar has its own charm, in addition to the inn, there are also beautiful scenery, learn about local culture, enjoy art exhibitions, enjoy local culinary imagery and learn handicrafts and pottery so that need a strategy in the management of Karanganyar Balkondes so that it is better known to the wider community and become an alternative tourist destination for domestic or foreign tourists when visiting Borobudur Temple. The KKN PPMT activities carried out by conducting “SADAR WISATA” education, mentoring and training in digital marketing, redesigning websites, redesigning street banners, event brochures, travel guides, culinary guides and optimizing social media are the implementation of e-business as a destination branding strategy for Balkondes Karanganyar. At the end of the program, it can be concluded that the implementation of e-business as a destination branding strategy is able to increase the knowledge and understanding of Balkondes Karanganyar managers so that promotion is more efficient and easily to access.